OsNCED5, a 9-cis-epoxycarotenoid dioxygenase gene, regulates salt and water stress tolerance and leaf senescence in rice. (October 2019) - Huang, Yuan; Jiao, Yang; Xie, Ningkun; Guo, Yiming; Zhang, Feng; Xiang, Zhipan; Wang, Rong; Wang, Feng; Gao, Qinmei; Tian, Lianfu; Li, Dongping; Chen, Liangbi; et al.
Highlights: OsNCED5 regulates tolerance to water stress and regulates leaf senescence in rice. It promotes plant development and stress resistance by controlling ABA biosynthesis. It regulates expression of genes related to abiotic stress and senescence. Abstract: 9- cis -epoxycarotenoid dioxygenase (NCED) is a rate-limiting enzyme for abscisic acid (ABA) biosynthesis. However, the molecular mechanisms of NCED5 that modulate plant development and abiotic stress tolerance are still unclear, particular in rice. Here, we demonstrate that a rice NCED gene, OsNCED5, was expressed in all tissues we tested, and was induced by exposure to salt stress, water stress, and darkness. Mutational analysis showed that nced5 mutants reduced ABA level and decreased tolerance to salt and water stress and delayed leaf senescence. However, OsNCED5 overexpression increased ABA level, enhanced tolerance to the stresses, and accelerated leaf senescence. Transcript analysis showed that OsNCED5 regulated ABA-dependent abiotic stress and senescence-related gene expression. Additionally, ectopic expression of OsNCED5 tested in Arabidopsis thaliana altered plant size and leaf morphology and delayed seed germination and flowering time. Thus, OsNCED5 may regulate plant development and stress resistance through control of ABA biosynthesis. These findings contribute to our understanding of the molecular mechanisms by which NCED regulates plant development and responses to abiotic stress in different crop species.